Critical Experiential Education: Re-Imagining Teaching and Learning - Small, Evan; Varker, Frannie (Experiential Learning and Teaching in Higher Education, 2023)
Understanding, complexifying, and co-generating space for critique, growth, and transformation through experiential education informs and helps re-imagine education in more equitable ways. Through a critical lens, critical experiential education offers the potential to engage students and educators alike in putting what educators re-imagine education to be into practice. A more equitable educational system calls for transforming our world into communities that are more generous, liberatory, kind, engaged, and appreciative of difference. The work of building these communities is the work educators and activists should focus on more now than ever in today's ever-changing and tumultuous world.